A Comparison of Fibula Pro-Tibia Fixation Versus Hindfoot Nailing for Unstable Fractures of the Ankle in Those Older Than 60 Years. Issue 2 (April 2023) - Eyre-Brook, Alistair Ian; Ring, Joseph; Chadwick, Carolyn; Davies, Howard; Davies, Mark; Blundell, Chris
Background: Ankle fractures in the elderly are an increasing problem, with poor outcomes reported. Operative options for patients with suspected osteoporosis and needing to bear weight to ambulate can include hindfoot intramedullary nail (IMN) or fibula pro-tibia fixation (FPT). FPT involves passing 2 or more screws through a lateral fibula plate, crossing the fibular into the tibia, with 1 or more screws proximal to the incisura. We compared the outcomes of these 2 techniques. Method: A retrospective review identified 68 patients aged over 60 years with unstable ankle fractures, treated with IMN or FPT. Primary outcome was surgical reoperation/revision rate, secondary outcomes included complications, length of stay, and functional status. Results: There were no significant differences in demographics between IMN and FPT. Revision rates were higher in IMN compared with FPT ( P < .0001). IMN patients postoperatively had longer hospital stays ( P = .02), longer follow-up times ( P = .008), and higher rates of delayed wound healing ( P = .03) and nonunion ( P = .001). Multivariate analysis identified fixation and age to affect revision rates. Conclusion: Outcomes were worse in the IMN group compared with FPT. We believe both techniques have a role in the management of elderly ankle fractures, but patient selection is key. We suggest that FPT should be the first-choice technique when soft tissues permit. Levels of Evidence: Level III